2009
DOI: 10.1002/ejic.200900780
|View full text |Cite
|
Sign up to set email alerts
|

Activation and Deactivation of Cp*Ir(TsDPEN) Hydrogenation Catalysts in Water

Abstract: The addition of H3PO4 to Cp*Ir(TsDPEN‐H), where TsDPEN = H2NCHPhCHPhNTs–, is a simple method to obtain a water‐soluble hydrogenation catalyst capable of reducing aromatic ketones to their corresponding alcohols in aqueous solutions. Key to the reactivity is the low affinity of the coordinatively unsaturated [Cp*Ir(TsDPEN)]+ for H2PO4–. Catalyst degradation proceeds via the protonation of the tosylamido ligand, as was established by the crystallographic characterization of the tosylamine complex [Cp*Ir(NCMe)(HT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 23 publications
1
19
0
Order By: Relevance
“…Similarly to somewhat related complexes,12, 21 the aminopyridinate iridium compound 1 (Scheme ) that contains an {(η 5 ‐C 5 Me 5 )Ir III } unit and an aminopyridinate group in which the amido functionality acts as a σ‐ and π‐donor ligand, reacted with H 2 (CH 2 Cl 2 , 1 atm) to yield a known dinuclear trihydride,22 along with an equimolecular mixture of the free and protonated aminopyridine, HAp and [H 2 Ap]BAr F , respectively (BAr F − =B[3,5‐(CF 3 ) 2 C 6 H 3 ] 4 − ). Before reaching completion, NMR studies of the reaction mixture revealed the presence of small amounts of unreacted 1 and of a third metal‐containing product, 2 , which was subsequently isolated and characterized as an isomer of 1 with the structure shown in Figure 1.…”
Section: Methodsmentioning
confidence: 87%
“…Similarly to somewhat related complexes,12, 21 the aminopyridinate iridium compound 1 (Scheme ) that contains an {(η 5 ‐C 5 Me 5 )Ir III } unit and an aminopyridinate group in which the amido functionality acts as a σ‐ and π‐donor ligand, reacted with H 2 (CH 2 Cl 2 , 1 atm) to yield a known dinuclear trihydride,22 along with an equimolecular mixture of the free and protonated aminopyridine, HAp and [H 2 Ap]BAr F , respectively (BAr F − =B[3,5‐(CF 3 ) 2 C 6 H 3 ] 4 − ). Before reaching completion, NMR studies of the reaction mixture revealed the presence of small amounts of unreacted 1 and of a third metal‐containing product, 2 , which was subsequently isolated and characterized as an isomer of 1 with the structure shown in Figure 1.…”
Section: Methodsmentioning
confidence: 87%
“…Similarly to somewhat related complexes, [12,21] the aminopyridinate iridium compound 1 (Scheme 2) that contains an {(h 5 -C 5 Me 5 )Ir III } unit and an aminopyridinate group in which the amido functionality acts as a s-and p-donor ligand, reacted with H 2 (CH 2 Cl 2 , 1 atm) to yield a known dinuclear trihydride, [22] along with an equimolecular mixture of the free and protonated aminopyridine, HAp and [H 2 Ap]BAr F , respectively (BAr F À = B[3,5-(CF 3 ) 2 C 6 H 3 ] 4 À ). Before reaching completion, NMR studies of the reaction mixture revealed the presence of small amounts of unreacted 1 and of a third metal-containing product, 2, which was subsequently isolated and characterized as an isomer of 1 with the structure shown in Figure 1.…”
mentioning
confidence: 99%
“…[31][32][33][34][35][36][37][38][39] For example, metal complexes containing sulfonamide ligands have been used as catalysts in different organic reactions. [40][41][42][43] The transfer hydrogenation of ketones catalyzed by Ru(II) complexes bearing N-donor ligands has been attracting more and more attention from the catalysis community [44][45][46][47][48][49][50][51][52][53] since the success of Noyori's catalyst, bearing 1,2-diamine ligands. 54 Many derivatives of Ru(II) complexes containing N-donor ligands have been aimed to identify a good Ru(II) catalyst for the transfer hydrogenation of ketones.…”
Section: Introductionmentioning
confidence: 99%